Design, fabrication, modelling and analyses of a movable speed bump-based mechanical energy harvester (MEH) for application on road. (1st January 2021) - Azam, Ali; Ahmed, Ammar; Hayat, Nasir; Ali, Shoukat; Khan, Abdul Shakoor; Murtaza, Ghulam; Aslam, Touqeer
Abstract: In this paper, a novel mechanical energy harvester (MEH) based on a movable speed bump, which is integrated to a rack and gear mechanism with a combination of one-way clutches, is designed, fabricated and tested for application on the road. The device is capable of harvesting the kinetic energy that the decelerating vehicles dissipate in the form of vibrations during impact with the speed bump on the road, not only under loaded but also restoration conditions. The proposed harvester consists of four modules including energy input, transmission, energy conversion and storage. The up-down input motion of the bump is converted into bidirectional rotation by the transmission module, which is further transformed into unidirectional rotation of generator shaft by the continuous engagement and disengagement of one-way clutches. The mechanical energy is converted into electrical power by a DC generator that can be stored in batteries after rectification and used to light up the LED bulbs as electrical load. The operation of the MEH was modelled and simulation study was conducted in Solidworks and Autodesk Inventor to investigate and validate the dynamic response of the mechanism. A prototype was fabricated to determine the feasibility of the design and tests were performed to evaluate the output power from the MEH. A peak output power of 11.99 W and a peak voltage of 20.57 V was achieved at an excitation speed of 120 mm/s and applied force of 150 N. The experimental results were compared with the simulation and were found lying within accordance with each other at similar loading conditions. The proposed device would be able to power road lights, traffic cameras and signals which makes it suitable for application on the road, at the exit of the toll plaza and remote suburbs. Graphical abstract: Image 1 Highlights: An efficient mechanical energy harvesting system was designed for road applications. A novel mechanism was fabricated to harvest kinetic energy of the vehicles using speed bump. A simulation analysis and experimental study was conducted and validated on the prototype. A peak power output of 11.99 W and voltage of 20.57 V was obtained.